A Family-Centered Intervention to Monitor Children's Development in a Pediatric Outpatient Setting: Design and Feasibility Testing - Rasheed, Muneera A.; Mughis, Waliyah; Elahi, Kinza Naseem; Hasan, Babar S. (Frontiers in Health Services, 2021)
The patient experience team at a private tertiary care hospital used the theory of change to design a family-centered developmental monitoring intervention building on an ongoing initiative. The design entailed i) monitoring form: Survey of Well-Being of Young Children (SWYC) being an easy parent-report measure; ii) family support intervention: the Care for Child Development module to enhance parent-child interactions; iii) timing: utilize wait time to also enhance families’ experience and iv) the service providers: psychology trainee as volunteers; v) reinforcement: by the paediatrician in the regular consultation health visit capitalizing on the established rapport with families. All families with children under 5 years 5 months 31 days of age in selected acute, complex and developmental care clinics were eligible. Feedback from stakeholders indicated the monitoring process to be useful and important information for parents and paediatricians while the trainees felt the experience to be significant for their own learning. The authors conclude that the designed intervention model for a family-centric approach was acceptable and feasible. Key recommendations have been presented for further scale-up.